The Influence of Cultural Discourse on Tense Choice in English and Uzbek News Texts - Nigora Rejabova (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2026)
This study investigates the influence of cultural factors on tense selection in English and Uzbek news discourse through a comparative-typological analysis. The research framework draws on E. T. Hall’s theory of monochronic and polychronic cultures, G. Hofstede’s cultural dimensions model, F. Trompenaars’ time orientation models, the Sapir–Whorf hypothesis, and N. Fairclough’s Critical Discourse Analysis (CDA). The empirical analysis is based on a corpus of 1,000 news texts collected between 2023 and 2024 (500 English texts from BBC and CNN; 500 Uzbek texts from Xalq So‘zi, Kun.uz, and Daryo.uz). The results indicate a clear cross-linguistic difference in tense usage: Present Simple accounts for an average of 72% of English news headlines, whereas Past Simple represents approximately 80% of Uzbek headlines. Statistical analysis using the chi-square test (χ² = 487.32, p < 0.001) demonstrates that cultural factors exert a statistically significant influence on tense choice in media discourse. The contrasting temporal framing of identical events across the two media systems such as BBC: “President Mirziyoyev meets UK PM” versus Xalq So‘zi: “Prezident Mirziyoyev Buyuk Britaniya Bosh vaziri bilan uchrashdi” empirically illustrates how cultural conceptions of time shape linguistic representation in news reporting. The findings contribute to theoretical discussions on the interaction between language and culture and offer practical implications for linguistics, translation studies, journalism education, and intercultural communication.